2003
DOI: 10.1099/jmm.0.05171-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in tcpR gene (Vc0832) of Vibrio cholerae O1 causes loss of tolerance to high osmolarity and affects colonization and virulence in infant mice

Abstract: Vibrio cholerae, the agent of cholera, multiplies and colonizes human intestinal tract where it survives high osmolarity due to bile and other sodium salts. In this work, by TnphoA mutagenesis, a mutant of V. cholerae O1 which could not grow and form colonies on LB agar containing 400 mM NaCl has been characterized. The mutant, designated CD83, adhered normally to freshly isolated rabbit intestinal discs, colonized poorly the gut of infant mice and was avirulent in the same model, whereas the parent strain CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Vi-suppressing conditions (300 mM NaCl) encountered in the intestinal lumen (13,30,45) are difficult to mimic using tissue culture models, which rely on the use of tissue culture media containing 150 mM NaCl (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vi-suppressing conditions (300 mM NaCl) encountered in the intestinal lumen (13,30,45) are difficult to mimic using tissue culture models, which rely on the use of tissue culture media containing 150 mM NaCl (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…One hypothesis predicts that osmolarity may represent an important signal for the transition of S. Typhi from the lumen into intestinal tissue (36). In the intestinal lumen, the osmolarity is high, with values considered to be equivalent to 300 mM NaCl and greater (13,30,45). Once S. Typhi invades the intestinal bar-rier, it encounters a lower-osmolarity condition equivalent to ϳ150 mM (29), which has been reported to be the osmolarity of blood and plasma.…”
mentioning
confidence: 99%
“…In parallel, Na+ ions are also secreted into the small intestine [40]. As a consequence, after cholera toxin production [45], NaCl reaches high concentrations inside the intestine (> 300 mM) [46]. Thus, this coincides with the highest expression of the Pc proximal cassettes, and one can imagine that this gives a chance for the massively excreted bacteria to be better fit for the external unpredictable environment in which they will be released.…”
Section: Discussionmentioning
confidence: 99%
“…70,71 Furthermore, mutations in tcpR (a gene in the same operon as the pilus-colonizing factor TCP) results in a loss of tolerance to high osmolarity, defects in colonization, and attenuation of virulence, suggesting that this gene may be at least partially responsible for virulence in vivo. 72 A more recent study looking for changes in the transcriptional profile of bacteria grown in various NaCl concentrations revealed that large classes of genes (including those involved in pathogenesis, biofilm formation, exopolysaccharide synthesis, and solute transport) are differentially regulated in response to salt. A novel transcriptional regulator, OscR, whose expression is downregulated in response to increasing NaCl levels, was also identified in this study.…”
Section: Gastrointestinal Factors Alter Gene Expressionmentioning
confidence: 99%